Design and functionalization of bioactive benzoxazines. An unexpected ortho-substitution effect. (12th July 2019) - Arendt-Pindel, Agata; Marszałek-Harych, Aleksandra; Gębarowska, Elżbieta; Gębarowski, Tomasz; Jędrzkiewicz, Dawid; Pląskowska, Elżbieta; Zalewski, Dariusz; Gulia, Nurbey; Szafert, Sławomir; Ejfler, Jolanta
Abstract : A family of o, p - and N-functionalized dihydro-2 H -benzo-1, 3-oxazines was synthesized and characterized. Abstract : A family of o, p - and N-functionalized dihydro-2 H -benzo-1, 3-oxazines was synthesized and characterized. In vitro antimicrobial activity of the new benzoxazines was assessed against pathogenic fungi and Gram-negative and Gram-positive bacteria. The screened compounds showed significant in vitro antimicrobial effect, but introduction of the bulky substituent in the ortho position of the aryl ring caused a loss of their antibacterial efficacy. Cytotoxic assay results revealed that a molecule containing long alkyl chain substituents offered a remarkable viability of mouse fibroblast cells. Additionally, the liquid nature of alkyl-chain-modified monomers and the high processing windows indicate their high application potential.